High Energy, Sub-Cycle, Field Synthesizers - Wang, Haochuan; Alismail, Ayman; Barbiero, Gaia; Ahmad, Raja Naeem; Fattahi, Hanieh (IEEE Journal of Selected Topics in Quantum Electronics, 2019)
Tailoring the electromagnetic field transients has been a prominent research focus over the last decade. Advances in ultrashort pulse generation and stabilizing the carrier phase of the electromagnetic field relative to its envelope allowed for extension of coherent synthesis to optical frequencies and ultrashort pulse domain at tens of microjoules of energy. In parallel, ytterbium-doped lasers become a mature technology. They are able to deliver down to 1-picosecond scale pulses at hundreds of millijoule energy and kilowatt-scale average power, making them suitable frontends for scaling the energy and power of light transients. In this paper, we discuss two conceptual schemes, our experimental results, and technological challenges for generation of sub-cycle light transients based on Yb:YAG thin-disk lasers by direct and efficient spectral broadening of ytterbium-doped lasers, and by coherent combination of pulses from multiple broadband optical parametric amplifiers. Moreover, a conceptual design study for a novel synthesis scheme based on polarization splitting of a broadband spectrum and amplification of each polarization in a separate stage is presented. The novel sources hold promise for studying and controlling the nonlinear interactions of matter with custom-tailored light transients at a sub-cycle period of their electric field, opening up unprecedented opportunities in attoscience and strong-field physics.
CRIS-Team Scopus Importer:2023-04-20
Keywords: high harmonic generation; parametric amplifiers; pulse synthesis; Ultrabroadband sources; waveform nonlinear optics; Yb:YAG thin-disk laser